PENGARUH PUPUK UREA, PUPUK ORGANIK PADAT DAN CAIR KOTORAN AYAM TERHADAP SIFAT TANAH, PERTUMBUHAN DAN HASIL SELADA KERITING DI TANAH INCEPTISOL(The Effect of Urea, Solid and Liquid Organic Fertilizer from Chicken Manure to Soil Properties and The Yield of - Wiekandyne Duaja (Bioplantae, 2012)
The research was conducted at the green house of Faculty ofAgriculture, the University of Nusa Cendana, Kupang from July toSeptember 2012. The aim of this research were (1) to determine theeffect of urea, solid and liquid organic fertilizer from chicken manure tothe soil phisycs and chemistry properties, the growth and yield oflactuca sativa L, on inceptisol soil. This study was designed usingcompletely randomized design (CRD) with 6 treatments and 3replications. The treatments were without fertilizer (PO), 1 g ureapolibag-1 (P1), solid organic fertilizer 50 g polibag-1 (P2), 50 % of liquidorganic fertilizer (P3), 75% of liquid organic fertilizer (P4) and 100% ofliquid organic fertilizer (P5). There were 18 units of treatment. 100 %of liquid organic fertilizer (P5) equal with 50 g solid organic fertilizer(P2). Statistical analysis showed that: (1) The application of solid andliquid organic fertilizer from chicken manure gave significant effect onsoil organic carbon, soil bulk density, plant height, number of leaves,weight of root, and yield of lactuca sativa L. except on soil nitrogen, (2)Solid organic fertilizer from chicken manure gave the best effect on soilbulk density, organic carbon, number of leaf, the weight of fresh plantand roots of Lactuca sativa L, (3) from all the treatments of liquidorganic fertilizer, the concentration of 75% gave the best effect on thenumber of leaf compared to 50% and 100% of liquid organic fertilizer.Key words : chiken manure, Lettuce, growth, yield